2018
DOI: 10.1158/1078-0432.ccr-17-3125
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 4 Modulates TGFβ-Induced Aggressiveness in Triple-Negative Breast Cancer via SMAD2/3/4 and mTORC2 Signaling

Abstract: On the basis of the identified stress-independent cellular functions of activating transcription factor 4 (ATF4), we reported enhanced ATF4 levels in MCF10A cells treated with TGFβ1. is overexpressed in patients with triple-negative breast cancer (TNBC), but its impact on patient survival and the underlying mechanisms remain unknown. We aimed to determine effects on patients with breast cancer survival and TNBC aggressiveness, and the relationships between TGFβ and ATF4. Defining the signaling pathways may hel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
3
35
1
Order By: Relevance
“…c ). These candidates are key proteins in the cancer‐related pathways/processes mTOR2/AKT, TGFbeta and alternative splicing, respectively, and their expression has been shown to mediate poor outcome and resistance to therapy in different cancer types including thyroid cancer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c ). These candidates are key proteins in the cancer‐related pathways/processes mTOR2/AKT, TGFbeta and alternative splicing, respectively, and their expression has been shown to mediate poor outcome and resistance to therapy in different cancer types including thyroid cancer …”
Section: Resultsmentioning
confidence: 99%
“…3c). These candidates are key proteins in the cancer-related pathways/processes mTOR2/AKT, TGFbeta and alternative splicing, respectively, and their expression has been shown to mediate poor outcome 24,25 and resistance to therapy 26 in different cancer types including thyroid cancer. [27][28][29] We used TargetScan version 7.0 30 to search for hsa-miR-139-5p-matched sites within the 3'UTR sequence of the candidate genes and found one 7 mer-seed matched-site for each of them (Supporting Information Fig.…”
Section: Hsa-mir-139-5p Regulates the Expression Of Proteins Related mentioning
confidence: 99%
“…According to a study in 2018, overexpression of ATF4 can affect the survival rate of triple-negative breast cancer patients through SMAD2. [ 30 ] Moreover, there is strong evidence that silencing SMAD2 can inhibit TGF-β function. [ 31 ] However, a previous study showed that the absence of SMAD2 could lead to reduced differentiation and increased EMT levels, leading to tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SMAD2 is also involved in the regulation of many cancers. According to a study in 2018, overexpression of ATF4 can affect the survival rate of triple negative breast cancer patients through SMAD2 [31]. Moreover, there is strong evidence that silencing SMAD2 can inhibit TGFβ function [32].…”
Section: Discussionmentioning
confidence: 99%